Regulation of Cl- Electrolyte Permeability in Epithelia by Active Traditional Chinese Medicine Monomers for Diarrhea - Chen, Lei; Ding, Yan; Hou, Yapeng; Liu, Yanhong; Nie, Hongguang (Current Drug Targets, 2020)
The epithelial layer, lining the inner surface of the mammalian alveolar, kidney, brain and colon, is a typical electrolyte transporting tissue. Large quantities of salt and fluid are actively moved from the mucosal side toward the blood vessel. Transepithelial salt re-absorption in epithelial tissues plays an important role in maintaining fluid homeostasis. In absorptive epithelium, fluid and salt flux is controlled by the machinery mainly composed of epithelial sodium channel, cystic fibrosis transmembrane conductance regulator, Na+-K+-2Cl- cotransporter, Na+/H+ exchanger, and Na+/K+-ATPase. Dysregulation of salt permeability across epithelium contributes to the pathogenesis of organ edema. In numerous ion transporters, epithelial Cl- transportation plays an important role in water secretion across epithelial tissues and regulation of body fluid content. Many traditional Chinese medicines treat diarrhea by regulating the Cl- electrolyte transport. We systematically summarized the recent progress regarding the traditional Chinese medicine on Cl- electrolyte transport in the intestinal epithelial tissues. The pharmaceutical relevance of developing advanced strategies to mitigate edematous disorders is also implicated. In conclusion, the crosstalk between Cl- electrolyte transport and active traditional Chinese medicine monomers may lead to the development of new strategies for diarrhea by manipulating the function and expression of ion channels.
Keywords: diarrhea